SOCIAL SECURITY ISSUES FROM THE PERSPECTIVE OF ISLAMIC POLITICAL THOUGHT: A CASE STUDY OF INTER-RESIDENT BRAWLS IN BELAWAN, NORTH SUMATRA (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
Social security is a vital element of communal life, yet inter-resident brawls continue to occur frequently in Indonesia, one recurring case being in Medan Belawan District, North Sumatra, which has repeatedly caused material losses, injuries, and even fatalities, disrupting the stability of community life. This study aims to analyze the factors causing inter-resident brawls in Belawan, understand their impact on community social security, and examine the phenomenon from the perspective of Islamic political thought. The research uses a qualitative method with a case study approach; primary data were obtained through in-depth interviews with police officers, community leaders, perpetrators/former perpetrators of brawls, and victims' families, supplemented by secondary data from related documents and literature, using the Miles and Huberman interactive analysis model along with source and technique triangulation to ensure data validity. The results show that inter-resident brawls in Belawan are caused by an accumulation of interrelated factors, namely seemingly trivial everyday triggers, a culture of revenge and strong group solidarity, economic limitations and unemployment, and low levels of education and drug abuse, which, viewed from the perspective of Islamic political thought, contradict the principle of protecting life (hifz al-nafs) and the concept of islah, so that resolution needs to be directed toward realizing maslahah through a comprehensive preventive approach encompassing law enforcement, economic empowerment, education, religious guidance, and the sustained strengthening of the roles of family and community.